(untitled) (Eurasian Journal of Engineering and Technology, 2022)
The article describes the condition of power transformers that have been operating under operating conditions for a long time. The article is devoted to the issues of extending the service life of these power transformers, taking into account the economic state of the electric power system today. The analysis of scientific publications devoted to the problem of increasing the reliability of high-voltage transformers with an integrated approach to assessing their reliability is carried out. The problems of using the existing complex of high voltage transformers are analyzed. To assess the technical condition of transformers, factors leading to damage and failure of power transformers during their operation, the available regulatory materials are analyzed. The development of methods for monitoring the technical condition of high-voltage electric transformers, as well as the establishment of the boundaries of decision-making criteria for their further operation are important for improving the reliability of the complex of electric transformers operating at power plants and substations of the electric networks of Uzbekistan. Based on the best foreign experience, the necessity of conducting a number of theoretical and experimental studies with the development of appropriate methods and criteria for the Republic of Uzbekistan is substantiated